Phonological Repetition of Paul Laurence Dunbar's Selected Poems - Nana Nurmayanti; Famala Eka Sanhadi Rahayu; Jonathan Irene Sartika Dewi Max (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
The study of stylistics involves the examination of language, particularly the exploration of language in creativity. Analyzing literary works using stylistics can enhance the understanding of language in meaning-making. The purpose of this study is to describe the types of repetition identified in the selected poems of Paul Laurence Dunbar and to describe and find the function of repetition. This research utilized a qualitative research methodology with a stylistic approach that aims to identify the types and functions of repetition in Paul Laurence Dunbar’s selected poems. The results of this research found all types of repetition; there are ninety-seven alliterations, one hundred and twenty-eight assonances, eighty consonants, eight feminine rhymes, seventy-two masculine rhymes, four internal rhymes, thirteen end rhymes, four near rhymes, and six refrains. After analyzing and identifying the data, the researcher also found all four functions of repetition in Dunbar's selected poems. The functions of repetition found are reinforcing meaning, emphasizing certain words, imitating certain actions, and connecting or contrasting words. Assonance was the most common type of repetition used by Dunbar. Meanwhile, the most common function found was emphasizing certain words. Assonance has the role of creating musicality and rhythm, which can enhance the lyrical quality of language. Furthermore, the repetition of vowel sounds can enhance the emphasis of meaning. The function of assonance is in certain words, which allows the writer to communicate and convey the message through the choice of words in poems. It can help readers understand and reinforce the ideas that are being conveyed. Studi stilistika melibatkan pemeriksaan bahasa, khususnya eksplorasi bahasa dalam kreativitas. Menganalisis karya sastra menggunakan stilistika dapat meningkatkan pemahaman bahasa. Tujuan dari penelitian ini adalah untuk mendeskripsikan jenis-jenis repetisi yang teridentifikasi dalam puisi-puisi pilihan Paul Laurence Dunbar dan juga untuk mendeskripsikan dan menemukan fungsi repetisi. Penelitian ini menggunakan metodologi penelitian kualitatif dengan pendekatan stilistika yang bertujuan untuk mengetahui jenis-jenis dan fungsi repetisi dalam puisi-puisi pilihan Paul Laurence Dunbar. Hasil penelitian ini menemukan semua jenis repetisi, terdapat sembilan puluh tujuh aliterasi, seratus dua puluh delapan asonansi, delapan puluh konsonan, delapan sajak feminin, tujuh puluh dua sajak maskulin, empat sajak internal, tiga belas sajak akhir, empat sajak dekat dan enam refrain. Setelah menganalisis dan mengidentifikasi data, peneliti juga menemukan keempat fungsi repetisi dalam puisi-puisi pilihan Dunbar. Fungsi repetisi yang ditemukan ialah, memperkuat makna, menekankan kata-kata tertentu, meniru tindakan tertentu, dan menghubungkan atau membedakan kata-kata. Asonansi adalah jenis repetisi yang paling umum digunakan oleh Dunbar. Sementara itu, fungsi yang paling umum ditemukan adalah untuk menekankan kata-kata tertentu. Asonansi memiliki peran untuk menciptakan musikalitas dan ritme, yang dapat meningkatkan kualitas liris dari bahasa. Selanjutnya, pengulangan bunyi vokal dapat meningkatkan penekanan makna. Fungsi asonansi adalah untuk menekankan kata-kata tertentu, yang memungkinkan penulis untuk berkomunikasi dan menyampaikan pesan melalui pilihan kata dalam puisinya. Oleh karena itu, hal ini dapat membantu pembaca memahami dan memperkuat gagasan yang ingin disampaikan.